Upper Cervical Spine Fusion in Children With Skeletal Dysplasia. (September 2013) - Pakkasjärvi, N.; Mattila, M.; Remes, V.; Helenius, I.
Background: Skeletal dysplasias have been associated with upper cervical instability. Many patients are initially asymptomatic, but the instability may progress to subluxation and dislocation and complications thereof, including death. Surgery is hampered by petite osseous structures and low bone formation rate. Aim: To review the outcomes of surgical fusion of upper cervical instability in children with rare skeletal dysplasias. Material and Methods: A retrospective study of eight children with five different rare skeletal dysplasias needing upper cervical instrumented stabilization. Cases were evaluated for clinical, radiologic, and quality-of-life outcomes, with median follow-up time of 5 years. Results: Six patients underwent posterior, segmental cervical spine instrumentation and fusion (three C1/C2 fusions, three occipitocervical fusions), one anterior cervical instrumented spinal fusion, and one anteroposterior fusion. Autogenous bone grafting was used in all patients, and seven were immobilized using a halo body jacket. Nonunion in occipitocervical fusions was common in these patients (3/8 patients). Rib autograft from occiput to cervical spine with recombinant human BMP-2 was used to salvage nonunions. Conclusions: Surgical fixation in the pediatric cervical spine is hampered by fragile posterior structures. A postoperative immobilization by halo vest for 4 months is customary. Selective anterior corpectomy and plate fixation is not recommended in pediatric patients with skeletal dysplasias. Level of Evidence: Level 4, Case Series